Shiga toxin producing Escherichia coli-associated diarrhea and hemolytic uremic syndrome in young children in Romania - Falup-Pecurariu, Oana; Lixandru, Raluca Ileana; Cojocaru, Emanuela; Csutak, Katalin; Monescu, Vlad; Muhsen, Khitam; Falup-Pecurariu, Cristian; Cohen, Daniel (Springer Science and Business Media LLC, 2019)
Background Diarrheagenic Escherichia coli (E. coli) is an important cause of diarrheal diseases in both developing countries and industrialized countries. An outbreak of hemolytic uremic syndrome (HUS) in young children from southern Romania was reported in early 2016 and was attributed to Shiga toxin producing E. coli (STEC) O26 infection. The aim of this study was to determine the prevalence, demographic and clinical characteristics of STEC infections in children hospitalized with diarrhea in Brașov in the central region of Romania. We also described the occurrence of HUS among hospitalized children, close in time to the 2016 HUS outbreak in southern Romania. Methods A prospective study was conducted between March and December 2016 among 722 children aged 1–30 months hospitalized with acute diarrhea. Stool samples obtained from patients with diarrhea were tested for the presence of Shiga toxin type 1 (STX1) and type 2 (STX2) by an immunochromatographic assay, and other enteropathogens. Demographic and clinical information on cases of HUS diagnosed in the same hospital was obtained from medical records. Results Overall 46/722 (6.4%) children (mean age 10.3 months, 32.6% females) hospitalized with diarrhea tested positive for STX1 or STX2; of these 79% were positive for both STX1 and STX2, 16% for STX2 only, and 5% for STX1 only. Bloody diarrhea, vomiting and fever were documented in 32.6%, 52.1% and 50.0%, respectively of patients with STEC infection. Eleven confirmed HUS cases (mean age 20 months, five females) were identified between 2014 and 2016 with prodromal diarrhea reported in 10 of them. Three of the 11 HUS patients required hemodialysis. Conclusions STEC prevalence among young children with diarrhea in Romania was high and the risk of HUS is emerging. The establishment of a systematic laboratory-based surveillance program including identification of the circulating STEC strains coupled with epidemiological investigation of HUS patients is warranted to determine the source and mode of transmission of STEC and prevent of STEC-associated diarrhea and HUS.